EKSPLORASI FILOSOFIS ALAT MUSIK TRADISIONAL ADITIA MASYARAKAT DESA PADANG PANJANG KECAMATAN ALOR TIMUR - Elisabeth Labe; Dorkas Penau; Halena Muna Bekata; Eflin M. E Kelamau; Doni R. P. Beri; Drasmi I. Kamata; Petrus Mau Tellu Dony (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The purpose of this research is to present the Philosophical Exploration of Adatia Traditional Musical Instruments of the Community of padang panjang village, alor timur sub-district. The research data analysis used qualitative descriptive analysis. The data used in the research is qualitative data. The data collection technique was carried out in two ways, namely field observation and interviews. This research was conducted in Padang Panjang Village, East Alor District, Alor Regency. The information in this study is a traditional leader. The results of this study indicate that: (1) the use of traditional musical instruments; (2) magna traditional musical instruments; (3) musical instruments can be used in various activities. The results of this study can be concluded that the Padang Panjang Village Community has an interesting traditional musical instrument tradition.